MEDIA TIKTOK DAN DAMPAKNYA TERHADAP KEINGINAN MENIKAH DINI PADA REMAJA KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Pebriandy , Hapip; Muslikhah , Febri Palupi; Yusnita , Titien (Fakultas Ilmu Dakwah dan Komunikasi, 2023)
The increase in cases of early marriage in Indonesia is something that must be considered, Pamijahan District is one of the highest sub-districts with cases of early marriage of 688 couples. This is due to the increasing use of social media, one of the most frequently used social media, especially in their teens, is TikTok social media. In 2019-2022, TikTok social media has become one of the most downloaded and accessed applications by Indonesian people. This study aims to determine the effect of social media TikTok on the attitude of early marriage in adolescents in Pamijahan Subdistrict, as many as 351 respondents became the sample of this study, namely students at Al-Amin High School, Pamijahan 1 High School, Ibnu Hajar High School, and Al- Ijtihad High School. This study used the non-parametric method of the Chi Square test with data collection using a google form and a questionnaire. By using SPSS and carrying out the Chi Square Test, the Sig values of all independent variables (X) with respect to Y were obtained at a Sig value of <0.05. The results of this study are social media TikTok influences the attitude of early marriage in adolescents in Pamijahan District.